1987
DOI: 10.1128/jb.169.12.5496-5503.1987
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and expression in Escherichia coli of Acinetobacter calcoaceticus genes for benzoate degradation

Abstract: The catabolic genes necessary for the conversion of benzoate to catechol have been cloned from Acinetobacter calcoaceticus into Escherichia coli. The cloned genes, benABCD, encoded both a benzoate 1,2-dioxygenase system, composed of NADH-cytochrome c reductase and terminal oxygenase components, and a cis-diol dehydrogenase. The dioxygenase system appears to be encoded by three genes, benABC, whose products, 53-, 19-, and 38-kilodalton proteins, correspond in size to those of components in other bacterial dioxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
0
2

Year Published

1991
1991
2001
2001

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 48 publications
3
68
0
2
Order By: Relevance
“…This microbe has genes in the order benP benK benM benABDE (4,26). Biochemical evidence indicates that the Acinetobacter benA, -B, and -C genes encode benzoate 1,2-dioxygenase and the benD gene encodes 2-hydro-1,2-dihydroxybenzoate dehydrogenase (39). The Acinetobacter benK gene encodes a benzoate transporter (5).…”
Section: Discussionmentioning
confidence: 99%
“…This microbe has genes in the order benP benK benM benABDE (4,26). Biochemical evidence indicates that the Acinetobacter benA, -B, and -C genes encode benzoate 1,2-dioxygenase and the benD gene encodes 2-hydro-1,2-dihydroxybenzoate dehydrogenase (39). The Acinetobacter benK gene encodes a benzoate transporter (5).…”
Section: Discussionmentioning
confidence: 99%
“…In the wellcharacterized Acinetobacter sp. ADP1, a close physical association between the ben and cat gene clusters is evident, but the gene clusters are still distinctly separate (Collier et al, 1998 ;Neidle et al, 1987). Although the cbe and cat genes are also clustered in NK8, there are significant differences between ADP1 and NK8 in terms of the organization of the corresponding genes in the cluster.…”
Section: The Convergent Organization Of the Cbe-cat Gene Clustermentioning
confidence: 99%
“…(Haak et al, 1995), X79076 ; XylXYZ (toluate 1,2-dioxygenase) and XylL (toluate diol dehydrogenase) of Pseudomonas putida mt-2 TOL plasmid pWW0 , M64747 ; BenABC (benzoate 1,2-dioxygenase) and BenD (DHB dehydrogenase) of Acinetobacter, sp. ADP1 (Neidle et al, 1987), AF009224 ; AntABC (anthranilate dioxygenase) of Acinetobacter sp. ADP1 (Bundy et al, 1998), AF071556 ; and TftAB (2,4,5-trichlorophenoxyacetate oxygenase) of Burkholderia cepacia AC1100 (Danganan et al, 1994) Nucleotide sequence analysis of this 12n5 kb DNA region revealed the presence of 9 ORFs.…”
Section: Cloning and Sequencing Of The Chlorobenzoate Dioxygenase Genesmentioning
confidence: 99%
“…In the following plasmid descriptions, the restriction endonuclease site positions correspond to the 15,923-nucleotide sequence of the ben-cat region in GenBank, accession number M76991. A. calcoaceticus DNA on plasmid pIB1381 (22) was deleted between the SmaI and SspI sites, positions 4,416 and 5,983, respectively, to generate pIGG21. This deletion eliminated the 5Ј end of the catA gene and part of an open reading frame upstream of catA (25).…”
Section: Methodsmentioning
confidence: 99%